(untitled) (diségno, 2026)
In the urban landscape that had seen a strong adherence to languages based on neoclassical eclecticism, as a requirement for civic decorum, during the pre-war reconstruction phase, Messin’s residential architecture, between the 1950s and 1960s, participated in the national and international debate, assimilating the linguistic codes of the Modern Movement and the International Style. The new multi-story collective buildings, located in vacant blocks or completing undeveloped areas, brought references to a modern home in both their language and their amenities. The aspiration toward international modernity also became a social connotation. It was primarily engineers, designers, and builders who undertook syntactic reinterpretations in which the language of the façade developed new and bold solutions, in line with technical experimentation. The openness to new modern and rationalist tendencies nevertheless allowed for the ability to unify the architectural composition starting from structural data. The facades are arranged within the urban block, sometimes as separate parts, in terms of height, colour, and materials, other times perfectly inserted into the regularity and scale of the rigid urban grid.